Influence of Social Media Marketing Strategies and Best Practices on E-Satisfaction And E-Loyalty - Suzette Colonia Quico (Faculty of Economics, Universitas Sriwijaya, 2023)
This study investigated hotels' social media marketing strategies in Davao Region. This study used mixed method with explanatory sequential. The respondents for research survey were 455, while there were 8 respondents for in-depth interviews. Data revealed that social media is one of the most cost-efficient digital marketing methods; Facebook is the most prevalent Social Networking Site (SNS) used by hotels and uses third- party booking sites to support the hotel's revenue. The results of this study show that selected hotels implemented a high level of effectiveness of social media, a high level of customers' esatisfaction on social media, and a high level of e- loyalty of hotels' customers on social media marketing strategies by hotels. Thus, the result clarified that compared to social media marketing, e-satisfaction, as a factor in general, was influential in igniting e-loyalty. Lastly, three best practices were identified by the participants: innovation, accessibility, and customer engagement.